Multimodal Analysis of Facial Symmetry, Skin Biomechanics and Patient-Reported Outcomes Following Minimally Invasive Aesthetic Procedures - Abreen .; Imran Hussain; Suman Kumar Singh; Nirmala Rai; Puja Kumari (International Journal of Innovative Science and Research Technology, 2026)
Background: Photographs and overall impressions dominate many evaluations of minimally invasive facial procedures. However, facial symmetry, skin biomechanics, recovery, and patient-reported benefits are all separate outcome domains. This study aimed to combine objective and subjective outcome measures and their predictors for the first time, over 12 weeks. 150 adult patients were divided into 6 groups, each undergoing 1 of 6 selected minimally invasive facial procedures. Symmetry, skin elasticity, hydration, firmness, and wrinkles were assessed for each group, pre- and post- procedures, at 2, 6, and 12 weeks. A number of statistical analyses were conducted.